Mechanical Response of Industrial Concrete with SFRC and PFRC - José Ángel Ortíz-Lozano; Silvia Rodríguez-Narciso; Julián Carrillo; Juan Antonio Hernández-Andrade; Jesús Pacheco-Martínez; Martín Hernández-Marín; Albert de la Fuente-Antequera (Advances in Materials Science and Engineering)
Concrete is one of the most commonly used construction materials in the world due to its versatility. There are different types of concrete according to the required mechanical responses, and these will depend on the composition of the elements. Therefore, additional elements have been developed to improve the properties and conditions of concrete. One of these elements is reinforcing fibers made of steel, polypropylene, glass, and so on, which, according to the base material, geometry, and dosage, improve the mechanical and workability properties and decrease and/or prevent the generation of cracks, which are some of the most common problems in industrial slabs. This study performs an analysis of the changes in the mechanical properties of concrete (compressive strength, rupture modulus, modulus of elasticity, Poisson’s ratio, and residual stress) due to the addition of fiber-reinforced concrete (FRC) to determine the physical and mechanical conditions of the fibers that improve the concrete and its application in industrial concrete. Due to the large number of samples and variables, advanced statistical methods (analysis of variance and comparative index) were used in the numerical study, which allowed to analyze and compare several results at the same time. This research is divided into two stages. In the first stage, six steel fibers (with a dosage of 2.7, 6, and 11 and three of 28 kg/m3) and five polypropylene fibers (with a dosage of 0.6, 2.15, and 2.7 and two of 3 kg/m3) were used in the study, and compression and bending tests (ASTM C39 and C78, respectively) were performed on 35 cylinders and 45 beams. Improvements were identified in several fiber-reinforced concrete samples in terms of compressive strength: 67% of the steel fiber samples and 100% of the polypropylene fiber samples had values above the average value of the simple concrete; in terms of the modulus of rupture, 83% of the steel fiber samples and 80% of the polypropylene fiber samples had values above the average value of the simple concrete. In the second stage, one type of steel fiber and one type of polypropylene fiber were selected for a second mechanical analysis (64 cylinders, 72 beams, and 15 slabs) with dosages of 20, 30, and 40 kg/m3 and 2.13, 4.25, and 6.38 kg/m3, respectively. In the second stage, statistical analysis and modeling with nonlinear analysis were used to evaluate the results, where residual strength improved but Poisson’s ratio decreased when the dosage of fibers was increased.